2021
DOI: 10.1021/acsami.1c08926
|View full text |Cite
|
Sign up to set email alerts
|

MnO2-Based Nanomotors with Active Fenton-like Mn2+ Delivery for Enhanced Chemodynamic Therapy

Abstract: Chemodynamic therapy (CDT) is an emerging strategy for cancer treatment based on Fenton chemistry, which can convert endogenous H2O2 into toxic ·OH. However, the limited endocytosis of passive CDT nanoagents with low penetrating capability resulted in unsatisfactory anticancer efficacy. Herein, we propose the successful fabrication of a self-propelled biodegradable nanomotor system based on hollow MnO2 nanoparticles with catalytic activity for active Fenton-like Mn2+ delivery and enhanced CDT. Compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 56 publications
2
70
0
Order By: Relevance
“…As the concentration of the PP@Mn NPs increased, the MB absorption decreased, suggesting that the PP@Mn NPs produced abundant •OH ( Figure 1(J) ). The result was in accordance with previous report (Ou et al., 2021 ). Furthermore, to explore the influence of the photothermal effect on the Fenton-like reaction of the PP@Mn NPs, we placed the reaction systems in a water bath at 42 °C.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As the concentration of the PP@Mn NPs increased, the MB absorption decreased, suggesting that the PP@Mn NPs produced abundant •OH ( Figure 1(J) ). The result was in accordance with previous report (Ou et al., 2021 ). Furthermore, to explore the influence of the photothermal effect on the Fenton-like reaction of the PP@Mn NPs, we placed the reaction systems in a water bath at 42 °C.…”
Section: Resultssupporting
confidence: 94%
“…For the absorption time of 8 h, the PP@Mn NPs occupied approximately the entire cytoplasmic space. The fluorescence intensity of cellular Rho was quantified ( Figure 2(B) ), showing that the cellular uptake of the PP@Mn NPs increased within 8 h. The Mn 2+ in tumor cells can catalyze H 2 O 2 to •OH through the Fenton-like reaction (Liu et al., 2020 ; Ou et al., 2021 ). Moreover, tumor PTT can elevate the •OH level while improving the efficiency of the Fenton-like reactions (Liu et al., 2020 ; Zhou et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mn 2+ could not only consume GSH but also display Fenton-like properties. 64–66 Based on this, Xiaoyuan Chen et al constructed MnO 2 -based mesoporous silica nanoparticles (MS@MnO 2 NP). 67 Once taken up by cancer cells, the MnO 2 shell was used to oxidize GSH to accumulate H 2 O 2 , which led to RDH, ultimately enhancing Mn 2+ -mediated CDT.…”
Section: Regulation Of Reducing Species To Realize Rdhmentioning
confidence: 99%
“…Recently, heavy metal ions including iron [ 11 ], copper [ 12 ], and manganese [ 13 ], have been utilized to catalyze the conversion of endogenous hydrogen peroxide (H 2 O 2 ) to highly toxic hydroxyl radicals (·OH), whose accumulation then triggers reactive oxygen species (ROS)-mediated oxidative stress and non-programmed cell apoptosis; this process is termed chemodynamic therapy (CDT) [ 14 17 ]. Recently, Tao’s group reported that surface-oxidized arsenene nanosheets with oxygen vacancies also catalyzed a Fenton-like reaction, and then generate ·OH and O 2 from H 2 O 2 [ 18 ], which provided a completely new concept for developing highly efficient CDT agent.…”
Section: Introductionmentioning
confidence: 99%